Comparison of deltamethrin as indoor residual spray or on insecticide treated nets for mosquito control in Lake Chilwa - Pemba, Dylo F (The Medical Association Of Malawi, 2008)
We conducted a study on the control of mosquitos on Chisi Island in Lake Chilwa from August to November, 2006. The aim was to compare the cost and efficacy of deltamethrin, a pyrethroid based insecticide, when used in insecticide treated nets (ITN) and when used in indoor residual spray (IRS). Thirty village huts were enrolled in the study. Fifteen were systematically selected in a stratified manner and sprayed with deltamethrin following manufacturers' standard application procedures of 0.02g/m(2). The remaining fifteen were provided with ITNs. In both groups deltamethrin KO tabs were used. Pyrethroid knockdown (PKD) spray was used for indoor rest captures in the houses monthly for three months. Houses treated with IRS had significantly reduced number of mosquitoes resting indoors than houses provided with nets (p<0.05). Based on the prevailing market price of MK550 each, the cost of five nets was calculated as MK2750.00 per house hold of five compared to five 20g knock-out tablets costing MK300.00 using IRS. The cost of IRS is 10 times cheaper than ITN. These results suggest that it is cheaper and more effective to use deltamethrin in IRS than in ITN.